2019
DOI: 10.4274/tjh.galenos.2019.2019.0094
|View full text |Cite
|
Sign up to set email alerts
|

In silico study of correlation between missense variations of F8 gene and inhibitor formation in severe hemophilia A

Abstract: Amaç: F8 genindeki patolojik varyasyonlar, pıhtılaşma faktörü VIII'in (FVIII) azalmış ya da kaybolmuş aktivitesinden kaynaklanan ve kalıtsal bir kanama bozukluğu olan Hemofili A'ya neden olmaktadır. Tedavide en önemli zorluk, tedavi edici faktör VIII'e karşı inhibitör gelişimidir. Bu çalışmada F8 gen varyasyonlarının protein yapısı ve fonksiyonu üzerine olan etkilerini incelemeyi amaçladık. Gereç ve Yöntemler: Tüm testler CHAMP (CDC Hemofili A Mutasyon Projesi) veri tabanından bilgisayar hesaplama yöntemleriyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Moreover, a case of missense mutation was associated with a severe phenotype of hemophilia A and developed inhibitors. While many authors associate missense mutations with a low risk of inhibitor occurrence [19], Fodil et al reported a frequency of 13.51% of severe hemophilia A patients with missense mutations who developed inhibitors in their study [23]. According to their study, the risk of developing anti-FVIII inhibitors increases when the substitution results in an amino acid class change.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, a case of missense mutation was associated with a severe phenotype of hemophilia A and developed inhibitors. While many authors associate missense mutations with a low risk of inhibitor occurrence [19], Fodil et al reported a frequency of 13.51% of severe hemophilia A patients with missense mutations who developed inhibitors in their study [23]. According to their study, the risk of developing anti-FVIII inhibitors increases when the substitution results in an amino acid class change.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, in the missense mutation found in patient HA 56 during our study, arginine was replaced by histidine at position 2169. According to the amino acid distribution, arginine belongs to class 4 (basic), while histidine is polar, neutral, and belongs to class 2 [23]. Therefore, it is necessary to continue this study on a larger population to better understand these different mechanisms in the Beninese population.…”
Section: Discussionmentioning
confidence: 99%